Reading skill builders for Filipino children - Del Rosario, Virginia F. 1933- (s.n.], 1967)
Carefully worked out instructional materials and questions which would help in the development of different skills is provided in this study. Clarification of the use of some suggested procedures and techniques in the development of the various comprehension skills through the construction of skill builders for levels four, five and six are also presented. Through the construction and arrangement of the varied comprehension exercises, the dimensions of reading were shown.